Interaction of Islamic Education Values and Local Culture in the Architecture of Jami' Gresik Mosque, East Java - Siti Khumairotul Lutfiyah; Achmad Zaini; Noor Qurratina; Devi Celine (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
This article discusses the architecture of Masjid Jami' Gresik as a reflection of Islamic educational values and the acculturation of local culture. The research focuses on the importance of integrating Islamic values into the architectural design of mosques, which serve not only as places of worship but also as sources of education. The research method employed is qualitative with an anthropological approach, involving observation, interviews, documentation, and literature review. Data were collected through direct interaction with informants, including the management of Masjid Jami' Gresik, as well as analysis of relevant literature. The findings indicate that the architecture of Masjid Jami' Gresik not only reflects Islamic identity but also integrates elements of local culture that strengthen social relationships within the community. Islamic educational values, such as the values of faith, sharia, ethics, and aesthetics, are manifested in the design and function of the mosque. Thus, Masjid Jami' Gresik serves as a center for social and spiritual life that educates and empowers the community, creating an environment rich in meaning and identity.